Case Report: Investigation of the Time Evolution of Optical Breakdown Plasma During Irradiation of Aqueous Solutions of Fe Nanoparticles - Baimler, Ilya V.; Chevokin, Viktor K.; Podvyaznikov, Vitaliy A.; Gudkov, Sergey V. (Frontiers in Physics, 2021)
The time sweeps of images of optical breakdown plasma flashes under irradiation of aqueous solutions of Fe nanoparticles with Nd: YAG laser radiation (λ = 1064 nm, τ = 10 ns, ν = 10 kHz, ε = 2 mJ) are studied. It is shown that the sizes of plasma flares, the plasma glow intensity, and the time to reach the maximum intensity are concentrated around certain values. So, for example, the values of 30 μm are most typical for the maximum size of flares. The maximum luminescence is usually reached in 3-4 ns. It is found that at initial stage of optical breakdown process the water-vapor boundary moves at typical speed of 11 km/s and have maximum and minimum values at 15 km/s and 4 km/s respectively. It is assumed in this work that such a distribution may be associated with the initiation of breakdown on nanoparticles located in different places of the laser radiation waist.